The Grid Rotation Method and Its Application to the Glove Sizing System. Issue 1 (27th June 2012) - Lee, Cheol; Mo, Jeonghoon; Shin, Soeui; Lee, Kyungsik
Abstract In this article, we propose a grid rotation method for glove sizing to accommodate a greater fraction of the population with a given number of sizes. The method is based on the optimization of two geometric variables, the rotation degree and the number of grid points. Instead of applying a traditional tabulation method to the original samples, we apply the tabulation after rotating the sample points by a certain degree to improve coverage. We further optimize the grid points for the same purpose. Our results demonstrate the effectiveness of the proposed method. For the glove sizing system developed by the proposed grid rotation method, the coverage rate is increased by 2.3% compared to previous work for the same number of glove sizes.